EFFECTIVE COMPUTER MODELING IN EDUCATIONAL MANAGEMENT - Гращенко, І.С.; Краснюк, С.О.; Цалко, Т.Р.; Невмержицька, С.М.; Любимова, Н.В. (SWorldJournal, 2024)
Mathematical modeling in education management is a modern innovative tool for increasing the efficiency of management of educational processes. It allows you to create quantitative models of real processes, predict the results of decisions and optimize ma